Misoprostol For Induction Of Labor In Term Gestations At Maternal Perinatal National Institute, May 2009 - March 2010 - admin, admin (2018)
Objective. Misoprostol is an analogous of Prostaglandin E1, used for induction of labor when Bishop score is lower than 6. The goal of the study is to describe la eficacy of 25 μg vaginal misoprostol to induction of labor in term gestantions with live fetus. Also describe others outcomes like way of delivery, characteristics of newborn, adverse maternal and perinatal outcomes. Materials and methods. Descriptive and retrospective study. Population: pregnant women hospitalized in Obstetrics C Unit at Instituto Nacional Materno Perinatal for induction of labor with vaginal misoprostol. Period: may 2009 to march 2010. Data in SPSS version 13 to statistics analysis. Results. 25 μg vaginal misoprostol each 6 hours was administrated to 39 pregnants. Mean age was 27 years. Gestacional age 40 weeks (between 37 to 42). 51% was nulliparous, 92% pregnants had Bishop score lower than 5. It is achieved onset of labor in 87% and vaginal deliveries in 62%. Mild maternal outcomes was observed like chills and mild fever. 4 pregnants needed a cesarean for fetal distress and 1 for initial abruptio placentae. All of newborns had Apgar score adecuated, and no one of them needed hospitalization in Intensive Care Unit. Conclutions. 25 μg vaginal misoprostol is effective and safe to induction of labor in term gestations. It is recommended to perform a controlled clinical trial with a longer sample.